Lokale Klimaveränderung durch Flurbereinigung - Das Beispiel Kaiserstuhl - Endlicher, Wilfried (ERDKUNDE, 1980)
In the context of consolidation of land under viticuture in the wine growing district of the Kaiserstuhl the conventional small terrace relief is giving way to large terraces comprising several hectares each. This leads to considerable changes in the field climate,especially in respect of conditions of radiation and wind as well as surface and air temperature. With the aid of morning and midday thermal photography flights and measurement transits increasing risks of frosts and decreasing quality of yields could be proved to be the consequence of these reorganisations.